Unusual case of delayed pressure urticaria - Glińska, Olga; Kasperkowicz, Aleksandra; Gliński, Wiesław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Delayed pressure urticaria might represent a difficult diagnostic challenge for physicians since it may resemble other disorders. The purpose of recent study is to publish an unusual case of delayed pressure urticaria misdiagnosed over a 4 years period of recurrence of the lesions. A curiosity of this case were: 1) onset of the disease in childhood at age of 12, 2) development of urticarial lesions on restricted skin areas – mainly foot, 3) severe pain of lower extremities suggesting juvenile idiopathic arthritis. While chronic urticaria has been suspedted following causative factors were excluded tests: 1. allergic cause on the basis of negative skin prick tests with food and airborne allergens and normal serum IgE concentration, 2. autoimmune etiology by negative autologous serum intradermal test, 3. aspirin intolerance by elimination diet and negative response to oral provocation test with acetylosalicylic acid. On the other hand, the diagnosis of delayed-pressure urticaria has been confirmed by: 1) prolonged pressure stimulus (block test), during which 5 hrs after pressure application to the gluteal skin urticarial and oedematous lesions developed and were long lasted for about 12 hours, 2) good response to non-steroidal anti-inflammatory drugs, which induced complete remission of the lesions.